Ammonium tetrathiomolybdate following ischemia/reperfusion injury: Chemistry, pharmacology, and impact of a new class of sulfide donor in preclinical injury models. - Alex Dyson; Felipe Dal-Pizzol; Giovanni Sabbatini; Anna B Lach; Federica Galfo; Juliano Dos Santos Cardoso; Bruna Pescador Mendonça; Iain Hargreaves; Bernardo Bollen Pinto; Daniel I Bromage; John F Martin; Kevin P Moore; et al. (PLoS Medicine)
Background Early revascularization of ischemic organs is key to improving outcomes, yet consequent reperfusion injury may be harmful. Reperfusion injury is largely attributed to excess mitochondrial production of reactive oxygen species (ROS). Sulfide inhibits mitochondria and reduces ROS production. Ammonium tetrathiomolybdate (ATTM), a copper chelator, releases sulfide in a controlled and novel manner, and may offer potential therapeutic utility. Methods and findings In vitro, ATTM releases sulfide in a time-, pH-, temperature-, and thiol-dependent manner. Controlled sulfide release from ATTM reduces metabolism (measured as oxygen consumption) both in vivo in awake rats and ex vivo in skeletal muscle tissue, with a superior safety profile compared to standard sulfide generators. Given intravenously at reperfusion/resuscitation to rats, ATTM significantly reduced infarct size following either myocardial or cerebral ischemia, and conferred survival benefit following severe hemorrhage. Mechanistic studies (in vitro anoxia/reoxygenation) demonstrated a mitochondrial site of action (decreased MitoSOX fluorescence), where the majority of damaging ROS is produced. Conclusions The inorganic thiometallate ATTM represents a new class of sulfide-releasing drugs. Our findings provide impetus for further investigation of this compound as a novel adjunct therapy for reperfusion injury.